Angiotensin I‐converting enzyme inhibitory peptides derived from bovine casein and identified by MALDI‐TOF‐MS/MS. (26th September 2012) - Wu, Zhen; Pan, Daodong; Zhen, Xiaoqun; Cao, Jingxun
Abstract Background Hypertension is a major and common threat to the health of individuals around the world. Although agents such as captopril have been shown to regulate high blood pressure effectively, they bring unfavourable side effects such as dry cough and angioedema. If angiotensin I‐converting enzyme (ACE) inhibitors derived from natural substances such as milk proteins can be shown to be safe and efficient at managing hypertension, such inhibitors will be a valuable auxiliary to agents such as captopril. Results Low‐molecular‐weight casein‐derived peptides hydrolysed by cell envelope proteinase of Lactobacillus casei subsp. casei (ATCC 15008) showed quite high ACE‐inhibitory activity. The peptide fraction from α‐casein with molecular weight between 5 and 10 kDa showed the highest ACE‐inhibitory activity of 82.35%, with a 50% inhibition concentration (IC50) of 2.36 mg mL−1. Peptides from β‐casein exhibited lower ACE‐inhibitory activity (56.67%, IC50 4.00 mg mL−1). Three distinct peptide sequences derived from α‐casein (αs1‐cn f95–105, f106–115 and f148–166) were identified using two‐dimensional gel electrophoresis coupled with matrix‐assisted laser desorption/ionisation time‐of‐flight tandem mass spectrometry. Conclusion This work investigated the ACE‐inhibitory properties of casein‐derived peptides. Three distinct peptide sequences derived from α‐casein were identified. Characterisation of such peptides furthers the investigation of casein‐derived ACE‐inhibitory peptides from fermented dairy products.